The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/jnci/djw169
|View full text |Cite
|
Sign up to set email alerts
|

Night Shift Work and Breast Cancer Incidence: Three Prospective Studies and Meta-analysis of Published Studies

Abstract: Background: It has been proposed that night shift work could increase breast cancer incidence. A 2007 World Health Organization review concluded, mainly from animal evidence, that shift work involving circadian disruption is probably carcinogenic to humans. We therefore aimed to generate prospective epidemiological evidence on night shift work and breast cancer incidence.Methods: Overall, 522 246 Million Women Study, 22 559 EPIC-Oxford, and 251 045 UK Biobank participants answered questions on shift work and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
4
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(153 citation statements)
references
References 25 publications
8
129
4
8
Order By: Relevance
“…Night shift work has also been found to increase the risk of other cancers, including lung, colon, bladder, prostate, rectal, and pancreatic cancer as well as non-Hodgkin’s lymphoma [61,62,63]. However, a number of studies have found no association between cancer and shift work [64,65,66,67]. The variability in these findings may be related to other contributing factors, such as individual differences in susceptibility to carcinogenesis, occupational exposure to carcinogenic agents, and lifestyle [68,69].…”
Section: Cancermentioning
confidence: 99%
“…Night shift work has also been found to increase the risk of other cancers, including lung, colon, bladder, prostate, rectal, and pancreatic cancer as well as non-Hodgkin’s lymphoma [61,62,63]. However, a number of studies have found no association between cancer and shift work [64,65,66,67]. The variability in these findings may be related to other contributing factors, such as individual differences in susceptibility to carcinogenesis, occupational exposure to carcinogenic agents, and lifestyle [68,69].…”
Section: Cancermentioning
confidence: 99%
“…However, as with previous meta-analyses, there was significant heterogeneity in the characterization of NSW as a risk factor across the included studies. Moreover, as was identified in a recently published response to the Travis et al meta-analysis, the baseline age of women in the paper’s 3 prospective studies ranged from early-50 s to upper-60 s with follow-up periods of only 2–3 years (Travis et al, 2016; Schernhammer, 2017). This makes it challenging to support the authors’ claim that the “melatonin hypothesis” for breast cancer risk lacks merit, but gives credence to the IARC Working Group’s {IARC, 2009} argument for establishing greater consistency in operationally defining NSW as a risk factor.…”
Section: The Circadian Disruption and Breast Cancer Pathogenesis Modelmentioning
confidence: 98%
“…Kamdar and colleagues (Kamdar et al, 2013) did not find that participants working 8 or more years of NSW were at greater risk for developing breast cancer compared to non-shift workers, and Jia and colleagues (Jia et al, 2013) found that women working 15 or more years of NSW were not at increased risk above and beyond women who reported ever working night shift. The most recent meta-analysis (Travis et al, 2016) which included previously unpublished data from three prospective studies along with data from 7 published studies, found no significant associations among NSW and incident breast cancer risk (RR = 0.99, 95% CI = 0.95–1.03). However, as with previous meta-analyses, there was significant heterogeneity in the characterization of NSW as a risk factor across the included studies.…”
Section: The Circadian Disruption and Breast Cancer Pathogenesis Modelmentioning
confidence: 99%
“…Since the association between shift work and chronic diseases like CVD and breast cancer attenuates after cessation of exposure (6, 7), restricting study populations to elderly cohorts of former shift workers -who have not been exposed for years -may overlook real associations. The recent Million Women Study (8), which found no association between shift work and cancer, included subjects of very advanced age. Starting follow-up at an older age may have resulted in the inclusion of more participants less susceptible to the effects of night shift work (7,9).…”
Section: Selection Biasmentioning
confidence: 99%